PENGARUH KEMISKINAN, UMK DAN TINGKAT PENDIDIKAN TERHADAP JUMLAH PEKERJA MIGRAN KAPAL PESIAR ASAL PROVINSI BALI - Ningrat, Putu Shannia Krisna; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2023)
The purpose of this study was to determine the effect of poverty, minimum wage and education level on the number of cruise ship migrant workers from the province of Bali. This research uses secondary data from 2017-2022 obtained from BP2MI and BPS. The data collected was then analyzed using panel data regression techniques. The results of the study show that poverty has a positive and significant effect on the number of cruise ship migrant workers from the Province of Bali. The UMK has a negative and insignificant effect on the number of cruise ship migrant workers from the Province of Bali. The level of education has a negative and insignificant effect on the number of cruise ship migrant workers from the Province of Bali. The implication of this research is a consideration for the government to provide job training for the community so that apart from just passing formal education they are also trained to be ready to work after graduating from education. keyword : Cruise Ship, Poverty, UMK, Education Level.